2019
DOI: 10.31632/ijalsr.2019v02i02.001
|View full text |Cite
|
Sign up to set email alerts
|

Role of Probiotics in Health and Disease –A Review

Abstract: Human intestinal microbiota has undergone a lot of research in recent years and we are beginning to expand our knowledge of the role of bacteria, fungi, viruses and helminths in our gut in health and disease. Our gut contains myriad of over hundreds of millions of microbes that influence our body physiology, nutrition, metabolism, and immunity. A change in the type of these microbes has been shown to be associated with gastrointestinal diseases such as inflammatory bowel disease and systemic diseases like meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 43 publications
0
18
0
Order By: Relevance
“…Probiotics are functional foods that have been demonstrated to be effective treatments to control several diseases such as inflammatory bowel disease, allergy, diarrhea, etc. [7]. The gut is the key target for probiotics foods because it acts as the main interface between diet and metabolic pathways in human health as it modulates the intestinal microflora [8].…”
Section: Introductionmentioning
confidence: 99%
“…Probiotics are functional foods that have been demonstrated to be effective treatments to control several diseases such as inflammatory bowel disease, allergy, diarrhea, etc. [7]. The gut is the key target for probiotics foods because it acts as the main interface between diet and metabolic pathways in human health as it modulates the intestinal microflora [8].…”
Section: Introductionmentioning
confidence: 99%
“…According to the World Health Organization (WHO), probiotics are live bacteria that provide health benefits to the host when administrated in an adequate quantity. The use of living bacteria to treat gut diseases is as old as World War I when Alfred Nissle, a German physician and scientist, used an E. coli strain to treat diarrhea [ 68 ]. Now, different gut-associated microbial strains, typically from the genera Lactobacilli and Bifidobacteria , are available commercially as supplements to manipulate the gut microbiota to treat gastrointestinal related diseases.…”
Section: Gut Microbial Diversity Management Strategies To Treat Schiz...mentioning
confidence: 99%
“…This is mainly due to the administration of B. breve and B. longum. A review containing 8,014 infants, children and adult with acute diarrhea were given probiotics which contains Bifidobacterium strains, the result were found to reduce the duration of diarrhea 22 . Antibiotic associated diarrhea in children and adult patients are also recommended to take probiotics along with antibiotics this have proven antibiotic donot interfere with the probiotics 23 .…”
Section: Health Benefits Of Bifidobacterium Bifidobacteria In Diarrhoeamentioning
confidence: 99%
“…A recent study has reported that probiotic supplements containing B. longum and other species of Bifidobacterium, suppress the total number of colon cancer cells in rats 26 . Many studies have concluded that certain strains of probiotics can be used as an adjuvant in cancer treatment 22 .…”
Section: Bifidobacteria In Colorectal Cancermentioning
confidence: 99%